The Transformation of Online Academic Graphic Designers into Petite Bourgeoisie within the Digital Capitalism Ecosystem - Bangsa, Petrus Gogor; Udasmoro, Wening; Noviani, Ratna (Institut Seni Indonesia Yogyakarta, 2025)
Academic graphic designers possess strong cultural capital from higher education and deep knowledge of design. This capital includes academic qualifications, high technical skills, and extensive social networks. Internet technology opens global opportunities for them to leverage these skills. Through various digital platforms, they can showcase their work, obtain international projects, and join global communities. These platforms provide them with wide market access, enabling independent work and significant income. However, behind this freedom, they must follow platform rules that reduce their autonomy. Many academic designers then employ junior designers to expand their business, transforming into petite bourgeoisie within the digital economy, controlling junior labour while still subjected to the control of large digital capitalists. This practice creates a tiered exploitation, where senior designers extract more value from less experienced junior designers. This transformation shows that although internet technology and digital platforms open up significant opportunities, they also bring new challenges in the form of injustice and exploitation in the workforce, placing academic graphic designers at the intersection of economic freedom and structural dependency. Transformasi Desainer Grafis Akademis Online Menjadi Borjuasi Mungil dalam Ekosistem Kapitalisme Digital. Desainer grafis akademis memiliki modal kultural kuat dari pendidikan tinggi dan pengetahuan desain yang mendalam. Modal ini termasuk kualifikasi akademik, kemampuan teknis tinggi, dan jaringan sosial luas. Teknologi internet membuka peluang global bagi mereka untuk memanfaatkan keterampilan ini. Melalui berbagai platform digital, mereka bisa memamerkan karya, mendapatkan proyek internasional, dan bergabung dengan komunitas global. Platform ini memberi mereka akses pasar luas, memungkinkan kerja independen dan penghasilan signifikan. Namun, di balik kebebasan ini, mereka harus mengikuti aturan platform yang mengurangi otonomi mereka. Banyak desainer akademis kemudian mempekerjakan desainer junior untuk memperbesar usaha, berubah menjadi borjuis kecil dalam ekonomi digital, mengendalikan tenaga kerja junior namun tetap tunduk pada kontrol kapitalis digital besar. Praktik ini menciptakan eksploitasi berjenjang karena desainer senior mendapatkan nilai lebih dari desainer yunior yang kurang berpengalaman. Transformasi ini menunjukkan bahwa meskipun teknologi internet dan platform digital membuka peluang besar, mereka juga membawa tantangan baru berupa ketidakadilan dan eksploitasi dalam tenaga kerja, menempatkan desainer grafis akademis di antara kebebasan ekonomi dan ketergantungan struktural.